The Evaluation of Electronic Records Management Systems at Universities in Terms of Interoperability - Dişli, Meltem; Külcü, Özgür (Information World, 2020)
Universities use electronic records management systems (ERMS) in order to conduct internal correspondence faster, safer, more transparent and less costly. The interoperability of ERMS in the universities is important issue both for the integration of the ERMS and other systems within the institution and for the inter-organizational correspondence to be conducted in the electronic environment. In this research, current status of ERMS used in the universities in Ankara was investigated in terms of interoperability. The research included 104 personnel from the departments of all universities (9) accepting to contribute to the research and having ERMS in their organization. The findings obtained from the questionnaire were evaluated by making various statistical analyzes through SPSS software. As a result of the research, it was found that universities conduct inter-organizational correspondence through Registered Electronic Mail (REM), have trouble with REM, have no lack of legal infrastructure and troubles with suitability of guidelines and standards, the private universities have lack of technical infrastructure related to the interoperability, the level of awareness about interoperability in the state universities are higher than the private universities. In line with the results, various proposals were submitted to the university administrators, software companies and The Council of Higher Education.
Keywords: Electronic records management system; records management in the universities; interoperability; registered electronic mail; REM